The role of digital transformation in enhancing performance and security of technology infrastructure in public institutions - Saragih, Hondor (Edelweiss Applied Science and Technology, 2025)
Digital transformation has emerged as a critical enabler in enhancing the performance and security of technology infrastructure in public institutions. This study explores how the adoption of cloud computing, artificial intelligence (AI), and blockchain contributes to operational efficiency, improved decision-making, and robust cybersecurity measures in governmental organizations. Through a qualitative literature review approach, this research synthesizes findings from recent studies to assess the impact of digital transformation on public sector governance. The results highlight that digital transformation enhances service delivery, inter-agency collaboration, and data-driven decision-making, leading to increased institutional efficiency. Furthermore, cybersecurity remains a major concern, as public institutions are prime targets for cyber threats, data breaches, and ransomware attacks. The study identifies challenges such as outdated infrastructure, resistance to change, and the high cost of implementation, which hinder the seamless adoption of digital technologies. To address these challenges, it is essential for governments to invest in IT infrastructure, develop regulatory frameworks, and provide digital literacy training for employees. The study concludes that while digital transformation offers unparalleled opportunities for optimizing government operations, a comprehensive and well-structured strategy is required to mitigate risks and ensure long-term sustainability. Future research should focus on empirical case studies and best practices to guide policymakers and IT professionals in formulating more effective digital governance policies.